MEMAHAMI STRATEGI KOMUNIKASI KESATUAN AKSI MAHASISWA MUSLIM INDONESIA DI ERA DIGITAL - Dwi Candra Rini; Agus Naryoso; Sunarto Sunarto (Interaksi Online, 2023)
Extra-Campus Student Organizations have legally carried out internal campus activities. Indonesian Muslim Student Action Union or Kesatuan Aksi Mahasiswa Muslim Indonesia (KAMMI) is one of the Islamic-based Extra-Campus Student Organizations. Basically, there are no rules or legal basis related to the activities of extra-campus students in carrying out practical politics. However, each extra-campus student organization such as KAMMI still includes this prohibition in internal regulations, namely in the Statutes and Bylaws (AD/ART). This study aims to understand the communication strategy of KAMMI in the digital era. This research is a type of descriptive qualitative research with an ethnographic research design. This study uses data collection techniques with interview and observation methods. This study uses organizational control theory to explain the communication strategy of Kesatuan Aksi Mahasiswa Muslim Indonesia. The results of the study shows that the Kesatuan Aksi Mahasiswa Muslim Indonesia carries out a communication strategy through planning, implementation and evaluation. The Kesatuan Aksi Mahasiswa Muslim Indonesia uses a communication strategy with four organizational controls in accordance with the organizational control theory, which consists simple control, technical control, bureaucratic control, and concertive control.